Implementation Of Law Number 11 Of 2012 Concerning Child Related Criminal Justice System Concept Restorative Justice - Intan Karangan (Faculty of Law, Pattimura University, 2016)
This study aims to determine how the application of the concept of restorative justice in accordance with Law No. 11 of 2012 on Child Criminal Justice system. This study uses normative namely a study that discusses the problem based on the literature and legislation relating to the matter to be investigated. Law No. 11 of 2012 on the Criminal Justice System Child has provided a new concept in the criminal justice system, especially those in the juvenile justice system. Related to the concept of Restorative Justice or restorative justice is a resolution processes involving perpetrators, victims, families, and other relevant parties in a criminal act, jointly seek solutions to the offense and its implications by emphasizing restoration and not retribution.